Dialcohol cellulose spherical capsules
The development of spherical capsules with a dialcohol cellulose shell addresses the environmental concerns of traditional thermoexpansible microspheres by providing a sustainable, expandable capsule solution suitable for drug delivery and lightweight applications.
Patent Information
- Application Number
- JP2021543116
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-25
- Filing Date
- 2020-01-24
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-01-24
AI Technical Summary
Existing thermoexpansible microspheres are made from non-sustainable thermoplastic polymers and are not biodegradable, posing environmental concerns, and they lack the ability to form expandable hollow 'core/shell' type capsules.
Development of spherical capsules with a polymer shell made from optionally substituted dialcohol cellulose, which can be expanded after synthesis, using a process involving a solution containing dialcohol cellulose and non-polar organic compounds mixed with a poor solvent to form the capsules.
The use of dialcohol cellulose in the production of spherical capsules addresses the environmental concerns of non-biodegradable polymers and enables the creation of expandable capsules with improved compatibility and potential applications in drug delivery and lightweight materials.
Smart Images

Figure 0007671691000053 
Figure 0007671691000054 
Figure 0007671691000055
Abstract
Description
[Technical field]
[0001] The present invention relates to hollow spherical capsules made from cellulosic biopolymers and processes for their manufacture. [Background technology]
[0002] Thermally expandable microspheres are known in the art and are described, for example, in U.S. Pat. No. 3,615,972, WO 00 / 37547, and WO 2007 / 091960. Some examples are sold under the trademark Expancel®. Thermally expandable microspheres expand to form very low weight, low density fillers and can be used in applications such as foamed or low density resins, paints and coatings, cements, inks, and crack fillers. Consumer products that often contain expandable microspheres include lightweight shoe soles (e.g., for athletic shoes), textured covers such as wallpaper, solar reflective thermal insulation coatings, food packaging sealants, wine corks, artificial leather, foams for protective helmet liners, and automotive weather stripping.
[0003] Thermally expandable polymer microspheres usually contain a thermoplastic polymer shell and a hollow core containing a blowing agent that expands upon heating. Blowing agents include low boiling point hydrocarbons or halogenated hydrocarbons, which are liquid at room temperature but volatilize upon heating. To produce expanded microspheres, the expandable microspheres are heated such that the thermoplastic polymer shell softens, and the blowing agent volatilizes and expands, thus expanding the microspheres. Typically, the diameter of the microspheres can increase by 1.5 to 8 times during expansion.
[0004] A problem associated with the thermoplastic polymers typically used in microspheres is that they are not derived from sustainable sources. Typical monomers include those based on acrylates, acrylonitrile, acrylamide, vinylidene dichloride, and styrene, which are primarily derived from petrochemical sources. Furthermore, many polymers are not biodegradable, or at least biodegrade very slowly, thus posing a risk of cumulative buildup in the environment.
[0005] Hollow polymer spheres with larger dimensions can also be made, for example, on the millimeter scale. Hollow polymer spheres have potential for use, for example, as drug delivery agents, and therefore, the manufacture of hollow polymer spheres using biosourced polymers would be desirable to help improve the suitability and adoption of hollow polymer spheres.
[0006] For example, cellulose spheres can be made as described in Pettersson and Eriksson in Anal. Biochem., 2000, 285(2), 220-224. However, these are beaded spheres as opposed to hollow "core / shell" type capsules. Also, cellulose spheres tend to be inflexible and cannot expand once formed. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, there is a need for alternative biosourced or bio-derived polymers that can successfully form spherical capsules and / or microcapsules having core-shell structures, including those that can be expanded post-synthetically. [Means for solving the problem]
[0008] The present invention is directed to a spherical capsule comprising a polymeric shell surrounding a hollow core, the polymeric shell comprising an optionally substituted dialcohol cellulose.
[0009] The present invention is also directed to a process for preparing such spherical capsules, comprising mixing a solution comprising an optionally substituted dialcohol cellulose and one or more non-polar organic compounds with an anti-solvent to form spherical capsules having the above-mentioned properties, the anti-solvent comprising or consisting of the one or more compounds.
[0010] An antisolvent can be represented by the equation:
[0011]
number
[0012] Additionally or alternatively, the antisolvent may be represented by the equation:
[0013]
number
[0014]
number
[0015]
number
[0016]
number
[0017] Additionally or alternatively, the antisolvent may be C 1~6 Alcohol, C. 2~6 Diol, C 3~6 Triol, C 1~6 Haloalcohols, C 1~6 Halodialcohols, C 1~6 Alcohol ether, C 1~6 Glycol ether or glycerol ether, C 1~6 Ketones and diketones, C 1~6 Aldehyde, C 1~8 Haloether, C 1~6 Amine, C 1~6 Alcoholamine, C 1~6 Carboxylic acids and their anhydrides and C 1~4 Estelle, C. 1~6 Nitrile, C 1~6 Amides and their C 1~2 Alkyl N- or N,N-substituted derivatives, C 4~8 Cyclic anhydrides or amides, C 1~6 Organic sulfates and C 1~6 The anti-solvent may comprise or consist of one or more compounds selected from sulfoxides. Additionally, the anti-solvent may also comprise water.
[0018] Additionally or alternatively, the one or more non-polar organic compounds may have a solubility of less than 1% by weight in the anti-solvent.
[0019] In the following discussion, the terms "(substituted) dialcohol cellulose", "dialcohol cellulose and / or substituted dialcohol cellulose", and "optionally substituted dialcohol cellulose" have the same meaning. [Brief description of the drawings]
[0020] [Figure 1] 1 is a set of photographs of spherical capsules made using C1-2 alcohols or mixtures of water and C1-2 alcohols as antisolvents. [Diagram 2] Photographs of wet and air-dried capsules of dialcohol cellulose are shown. [Diagram 3] Electron micrographs of freeze-dried wet dialcohol cellulose capsules and air-dried capsules are shown. [Figure 4] 4 shows photographs of dialcoholcellulose capsules before and after swelling when suspended in water. [Diagram 5] Photographs of wet dialcohol cellulose capsules before and after expansion are shown. [Figure 6] 1 shows comparative photographs of wet capsules of dialcohol cellulose and cellulose before and after expansion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] In this disclosure, dialcohol cellulose refers to a form of modified cellulose in which at least some of the glucose monomer rings are opened. This is typically accomplished by oxidation, breaking the C2-C3 carbon-carbon bond to form two aldehyde groups, which are subsequently reduced to alcohol groups. The reaction can be represented by the following scheme (1):
[0022] [ka]
[0023] The formation of dialcohol cellulose from cellulose is well known and has been described, for example, in Kasai et al; Cellulose, 2014, 21, 769-776, Larsson et al; Cellulose, 2014, 21, 323-333, and Larsson and Wagberg; Green Chem., 2016, 18, 3324-3333. The general procedure involves treating cellulose or methylol cellulose (i.e., cellulose treated with formaldehyde and DMSO) with an oxidizing agent, e.g., a periodate salt such as sodium periodate (NaIO4), to form a ring-opened dialdehyde compound. The aldehyde group is then reduced to a hydroxyl group using a reducing agent such as a borohydride salt (e.g., NaBH4). The material so reduced is called dialcohol cellulose.
[0024] The degree of ring opening can be varied, for example, by changing the length of time the cellulose is held in contact with the oxidizing agent, the temperature of the treatment, and / or the relative ratio of cellulose to oxidizing agent. In an embodiment, the percentage of ring-opened glucose monomers in the cellulose (often referred to as the degree of oxidation) is up to 100%, such as up to 70%, for example up to 50% or up to 40%. In an embodiment, the percentage is at least 1%, such as at least 5% or at least 10%.
[0025] The extent of glucose ring opening of the dialcohol cellulose can be determined by calculating the carbonyl content of the cellulose after the oxidation step but before the reduction step. In an embodiment, the carbonyl content after the oxidation step but before the reduction step is between 0.001 and 12 mmol g -1 , e.g., 1-11, 3-9, or 5-8 mmol g -1These values can be determined using known methods such as the hydroxylamine hydrochloride based method described in Zhao and Heindel; Pharm Res 1991, 8(3), 400-402 and Larsson et al; Cellulose, 2008, 15, 837-847, as well as in Larsson et al, Cellulose, 2014, 21 on page 325.
[0026] The carbonyl content of the dialcohol cellulose after reduction is typically 0-10 mmol g -1 range, e.g., 0-7mmol g -1 Or 0-4mmol g -1 In embodiments, there is at least some carbonyl content, e.g., at least 0.001 mmol g -1 It is.
[0027] The degree of ring opening can also be correlated with the so-called crystallinity of cellulose. Unmodified cellulose has a crystalline structure. However, ring opening introduces amorphous regions, which are believed to result in improved ductility of cellulose, making it more suitable for forming spherical capsules, especially for expanding capsules.
[0028] The crystallinity of dialcohol cellulose can be determined by comparing the intensity of the cellulose (002) peak with the amorphous intensity, as shown, for example, in Larsson et al, Cellulose, 2014, 21, 323-333, especially page 327, based on Segal et al; Text. Res. J., 1959, 29(10), 786-794. The amorphous intensity can be measured from the minimum height between the (002) and (101) cellulose peaks.
[0029] In embodiments, the crystallinity is 80 or less, e.g., 50 or less. In further embodiments, the crystallinity is 30 or less. In embodiments, there is at least some crystallinity, e.g., the crystallinity is at least 1 or at least 10. Thus, exemplary ranges of crystallinity include 0-80, 0-50, or 0-30, e.g., 1-80, 1-50, or 1-30. In further embodiments, the crystallinity range is 10-80, or 10-50, e.g., 10-30.
[0030] The capsules are based on a polymer shell that comprises or consists of a dialcoholcellulose, which is optionally modified with one or more substituents as further described below.
[0031] The polymer shell may comprise one or more further polymeric components, which may also be selected from optionally substituted dialcohol celluloses.
[0032] In embodiments, the hydroxyl moieties on the dialcohol cellulose can be functionalized, for example, with one or more functional groups. Thus, the dialcohol cellulose can include one or more functional groups represented by the following formulas (1)-(3):
[0033] [ka]
[0034] In other embodiments, the dialcohol cellulose can additionally or alternatively contain aldehyde groups formed upon oxidation of the cellulose and / or functional groups based on the reaction of such aldehyde groups. Thus, the dialcohol cellulose can additionally or alternatively contain one or more groups according to the following formulae (4)-(7):
[0035] [ka]
[0036] In the above formulas (1) to (7), C g is a carbon atom that is part of the main chain of the dialcohol cellulose, that is, ( * ) is one of the atoms marked with
[0037] A is -H, -OR b , and -C(O)OR b In embodiments, A is selected from -H and -C(O)OH.
[0038] In formula (5), Y is oxygen or absent, i.e., C g and R b is a direct bond between
[0039] R a may be selected from saturated or unsaturated aliphatic groups having 1 to 11 carbon atoms and which may be linear, branched, or cyclic.
[0040] R a may also be selected from 5- and 6-membered aromatic rings.
[0041] R a -OH, halide, C 1~4 Alkyl and C 1~4 alkoxy, 1~4 Alkyl and C 1~4 The alkoxy group is optionally substituted with one or more groups selected from halide and -OH.
[0042] R of the embodiment a contains 1 to 7 carbon atoms, for example, 1 to 5 or 1 to 3 carbon atoms.
[0043] In formulas (2) to (7), when A is H, R a is optionally absent, A and R arepresents a chemical bond directly connecting the corresponding moieties of formulae (2)-(7) to which they would otherwise be attached. In an embodiment, the group R a -A is R b It may also be a group.
[0044] R per occurrence b H and C 1~4 Alkyl groups, e.g., C 1~2 In an embodiment, C is an alkyl group, optionally having one or more substituents selected from halide and -OH groups. 1~4 Alkyl group or C 1~2 The alkyl group is unsubstituted. In formulas (1) to (3), the group
[0045]
number
[0046] In embodiments, R a is a saturated linear or branched aliphatic
[0047]
number
[0048]
number
[0049] R per occurrence c H, -OH, halide, C 1~4 Alkyl, and C 1~4 alkoxy, 1~4 Alkyl and C 1~4 The alkoxy group is optionally substituted with one or more groups selected from halide and -OH.
[0050] In formula (3), y is an integer ranging from 1 to 4, and in embodiments, R b All occurrences of are H.
[0051] In an embodiment, in formulas (4) to (7), C n R above b The group is H.
[0052] In embodiments, R a is an unsaturated linear or branched aliphatic compound containing "y" double bonds.
[0053]
number
[0054] In a further embodiment, R a is an unsaturated cycloaliphatic compound containing "y" double bonds.
[0055]
number
[0056] In yet another embodiment, R a teeth
[0057]
number
[0058] In yet another embodiment, R a may be a linear or branched aliphatic group containing a cycloaliphatic or aromatic ring. Thus, R a has 11 or fewer carbon atoms
[0059]
number
[0060]
number
[0061] The halides are typically selected from F and Cl. However, in embodiments, the functional group is halide-free, such that the groups A, R a , R b , and R c There is no halide.
[0062] In an embodiment, at least one R c The group is H. In other embodiments, two of the following R c group is other than H, and in a further embodiment, only one R c Only the group is other than H. In yet another embodiment, R c All groups are H.
[0063] R a , R b , and R c In the above definition of , there may be multiple -OH substituents, typically only one -OH substituent per carbon atom.
[0064] In certain embodiments, R a is an optionally substituted C1-C8 aliphatic (alkylene) group. In other embodiments, R a is an optionally substituted C aromatic ring. In a further embodiment, R a is not substituted.
[0065] Substituted dialcohol cellulose materials can be prepared by known means. For example, carboxylate-functionalized materials (e.g., those of formula (2) above) can be prepared using the method of Nishio et al; Cellulose, 2006 (13), 245-259, or the method described in DE 102008024089 A1 can be used. Other condensation reactions (e.g., to form those of formula (1)) include acid-catalyzed condensation with alcohols or alkoxides. Materials with substituents of formula (3) can be prepared by alkali-catalyzed reaction with halocarboxylic acids (e.g., chloroacetic acid). For substituents of formulas (4)-(7), the groups can be prepared by conventional reaction of the non-reduced aldehyde groups formed when the cellulose ring is oxidized, as described above.
[0066] In embodiments, there are one or more substituents of formula (2), and the substituents are selected from acetate, propionate, butyrate, pentanoate, hexanoate, heptanoate, octanoate, and phthalate. In further embodiments, the substituents are selected from acetate, propionate, and butyrate.
[0067] The degree of substitution (DS) of the hydroxyl groups of the cellulose with one or more substituents can be in the range of 0 to 3.2, for example, in the range of 0 to 3. In an embodiment, the degree of substitution is zero, that is, a non-substituted dialcohol cellulose is used.
[0068] The degree of polymerization (DP) of the (substituted) dialcohol cellulose can be determined by conventional methods, for example, by using the alkaline size exclusion chromatography (SEC) method described in Kasai et al in Cellulose, 2014, 21, 769-776. Typically, the DP value is in the range of 100 to 10,000, for example, in the range of 200 to 6,000.
[0069] Glass transition temperature (T g) and melting point can be altered or controlled by varying the functional groups on the dialcohol cellulose, by varying the molecular weight, or by varying the degree of oxidation or hydroxylation of the cellulose.
[0070] The spherical capsules are hollow and have a core-shell structure, the shell comprises (substituted) dialcohol cellulose, and the hollow core contains a fluid, e.g., a liquid or gaseous component derived from a synthetic mixture. The core does not contain cellulose or a cellulose derivative, e.g., neither the crystalline cellulose phase nor the (substituted) dialcohol cellulose material present in the shell. Thus, the density of the spherical capsule is non-uniform, and the density of the polymer shell is higher than that of the fluid-containing hollow core.
[0071] The (substituted) dialcohol cellulose used to prepare the capsules has a mass of 1.2-1.7 g cm 3 , e.g., 1.35 to 1.60 g cm 3 The density may range from 0.01 to 0.01.
[0072] In an embodiment, the spherical capsule is expandable and the capsule has a density of 1.00 g cm -3 Less than, for example, 0.002 to 0.80 g cm -3 or 0.005~0.60g cm -3 In a further embodiment, the density of the expanded spherical capsules can be in the range of 0.008 to 0.40 g cm -3 At higher densities, especially at 1.00 g cm -3 Densities above this generally mean that the sample is not suitable for use in applications where sphere expansion is important, which are typically the cases where the volume of the material must be increased and / or density reduction is required, for example when used to prepare lightweight foam-like materials.
[0073] Considering the expandable properties of spherical capsules, several factors may result in the density after expansion being too high for effective utilization. For example, high density may result in poor capsule yield, i.e., the proportion of spherical capsules is too low, resulting in an insufficient degree of density reduction after expansion. Another potential problem is poor expansion properties, which may occur when too many hollow capsules contain insufficient expansion or blowing agent to allow proper expansion. This may be due to the shell being too permeable to the expansion / blowing agent, or due to the shell being too thick or too inflexible to allow expansion. Another potential cause is capsule clumping or agglomeration, which may negatively affect expansion performance.
[0074] In the synthesis of spherical capsules, the (substituted) dialcohol cellulose is typically first dissolved or dispersed in a solvent, which is typically an organic solvent, but can be in the form of an ionic liquid or a cooled aqueous alkali, for example an aqueous alkali metal hydroxide, where the alkali metal is typically selected from Li, Na or K. The solvent is selected so that solubilization of the (substituted) dialcohol cellulose is achieved. The solvent can be a solvent system that includes multiple components. For example, in embodiments, a lithium chloride solution in dimethylacrylamide can be used, as described by Berthold et al in J. Appl. Polymer Sci., 2004, 94(2), 424-431.
[0075] In an embodiment, the solvent also includes a non-polar organic compound, which can act as a cavity-forming agent and help form the hollow core of the spherical capsule during the synthesis procedure. The non-polar organic compound is at least partially soluble in a solution containing (substituted) dialcohol cellulose, for example, at a solubility of more than 1% by weight, for example at least 10% by weight, at 25° C. and atmospheric pressure (i.e., 1.013 bara, where "bara" stands for absolute bar). Also, the non-polar organic compound is insoluble or only partially soluble in the anti-solvent. For example, in an embodiment, the solubility in the anti-solvent is less than 1% by weight, and in an embodiment, less than 0.5% by weight, for example less than 0.1% by weight.
[0076] The non-polar organic compound may be the same as the so-called "blowing agent" often used in expanded foam or expandable microsphere applications. In this disclosure, the term "blowing agent" means the same thing as the "non-polar organic compound."
[0077] Non-polar organic compounds typically have boiling points greater than 25° C. at 5.0 bara pressure, or greater than 25° C. at 3.0 bara pressure. The boiling point at high pressure can be calculated using the Clausius-Clapeyron equation. Typically, non-polar organic compounds have boiling points greater than −50° C. at atmospheric pressure.
[0078] Non-polar organic compounds typically have a boiling point at atmospheric pressure of 250° C. or less, such as 150° C. or less or 50° C. or less. In embodiments, the boiling point at atmospheric pressure is less than 0° C.
[0079] The blowing agent is preferably inert and does not react with the cellulosic shell.
[0080] Examples of blowing agents include dialkyl ethers, alkanes, and halocarbons, such as chlorocarbons, fluorocarbons, or chlorofluorocarbons. In an embodiment, the dialkyl ether contains two alkyl groups each selected from a C2-C5 alkyl group. In an embodiment, the alkane contains a C3-C 12In an embodiment, the haloalkane is a C1-C 10 The dialkyl ether, the alkane, and the haloalkane may be selected from haloalkanes. The haloalkane may contain one or more halogen atoms selected from chlorine and fluorine. The alkyl or haloalkyl groups in the dialkyl ether, the alkane, and the haloalkane may be linear, branched, or cyclic. One or a mixture of one or more blowing agents may be used.
[0081] In an embodiment, for environmental reasons, the blowing agent(s) are selected from alkyl ethers and alkanes, and in a further embodiment, the blowing agent(s) are selected from alkanes. Haloalkanes are preferably avoided due to their potential ozone depletion properties as well as their large global warming potential.
[0082] Examples of suitable blowing agents that can be used include propane, n-pentane, isopentane, neopentane, cyclopentane, cyclohexane, n-butane, isobutane, isohexane, neohexane, heptane, isoheptane, octane, isooctane, isodecane, and isododecane. In embodiments, the blowing agent is selected from C3-C8 linear or cyclic alkanes. In other embodiments, the blowing agent is selected from C4-C8 linear or cyclic alkanes. 12 isoalkanes.
[0083] The blowing agent is typically selected to be insoluble in the water or aqueous phase of the synthesis mixture, but at least partially soluble or miscible with the anti-solvent.
[0084] The antisolvent is a liquid compound or liquid mixture of compounds that precipitates the (substituted) dialcohol cellulose. It can therefore alternatively be called a "precipitant" or a "precipitating agent". Liquid in this sense means a liquid at standard temperature and pressure (25°C and 1.013 bara). The antisolvent is miscible with water. However, the (substituted) dialcohol cellulose is insoluble or only partially soluble in the antisolvent. Partially soluble in this sense means that the (substituted) dialcohol cellulose has a solubility of 10% by weight or less in the antisolvent, for example, 5% by weight or less, or in an embodiment, 1% by weight or less.
[0085] The anti-solvent is less polar than water, so that water is not used as an anti-solvent as such. An embodiment of the anti-solvent has a polarity greater than that of methanol.
[0086] Polarity can be expressed by the dielectric constant ε at 20° C. When there are multiple components of a poor solvent, the dielectric constant can be calculated from the dielectric constants of each of the individual components, appropriately scaled based on their mole fraction in the mixture. This is expressed by Equation (1):
[0087]
number
[0088] When n is 1, a single compound is used in an antisolvent, and ε anti is the same as the dielectric constant of the single compound.
[0089] The above calculation may not faithfully represent the actual experimentally determined dielectric constant of the anti-solvent mixture, however, this definition (according to Equation 1) has been found to be sufficient to describe which compounds or mixtures of compounds can be used as anti-solvents.
[0090] The dielectric constant of water at 20°C is 80.10. Therefore, the dielectric constant of the poor solvent (ε anti ) should be less than 80.10. In embodiments, the dielectric constant is in the range of 20.0 to less than 80.0, e.g., in the range of 20.0 to 80.0. In embodiments, the dielectric constant is also greater than that of methanol, which has a dielectric constant of 33.0 at 20° C. Thus, in embodiments, the poor solvent has a dielectric constant (ε) greater than 33.0, e.g., greater than 33.0 to less than 80.1, or 34.0 to 80.0, e.g., in the range of 38.0 to 78.0, 45.0 to 75.0, 55.0 to 75.0, or 60.0 to 70.0. anti ).
[0091] Another way to express polarity is to use a relative polarity scale, which can be based on the shift in the UV / Vis spectroscopic absorption band of the solvatochromic dye in the presence of each solvent compared to a reference solvent. Such determinations are described, for example, by Reichardt in Chem. Rev., 1994, 94, 2319-2358. A dye that can be used is pyridinium N-phenolate betaine dye, which has a relative polarity value of
[0092]
number
[0093]
number
[0094]
number
[0095]
number
[0096]
number
[0097] For many common solvents
[0098]
number
[0099]
number
[0100] The calculated values for component mixtures may not necessarily match the experimentally determined values, but this definition (according to Equation 2) has been found to be sufficient to describe which compounds or mixtures of compounds can be used as antisolvents.
[0101] Alcohols (including diols and triols) are conveniently used as anti-solvents, but are typically used as a mixture in a more polar solvent, such as water. Some examples of solvents that can be included in the anti-solvent include C 1~6 Alcohol, C. 2~6 Diol, C 3~6 Triol, C 1~6 Haloalcohols, C 1~6 Halodialcohols, C 1~6 Alcohol ether, C 1~6 Glycol ether or glycerol ether, C 1~6 Ketones and diketones, C 1~6 Aldehyde, C 1~8 Haloether, C 1~6 Amine, C 1~6 Alcoholamine, C 1~6 Carboxylic acids and their anhydrides and C 1~4 Estelle, C. 1~6 Nitrile, C 1~6 Amides and their C 1~2 Alkyl N- or N,N-substituted derivatives, C 4~8 Cyclic anhydrides or amides, C 1~6 Organic sulfates and C 1~6and sulfoxides. In embodiments, each component of the anti-solvent has a dielectric constant of 20.0 or greater. Specific examples include mixtures of one or more of the following in water: methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, 2-chloroethanol, 3-chloro-1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, acetaldehyde, acetone, bis(2-chloroethyl)ether, 2,4-pentanedione, t-butylamine, formic acid, acetic anhydride, acetonitrile, butanenitrile, formamide, N-methylformamide, N,N'-dimethylacetamide, N,N-dimethylformamide, 2-pyrrolidone, dimethyl sulfate, epichlorohydrin, dimethylsulfoxide, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, diethylene glycol, triethylene glycol, glycerol, ethanolamine, diethanolamine, and triethanolamine.
[0102] In embodiments, the anti-solvent does not include halogen-containing or sulfoxide-containing compounds due to their potentially adverse environmental impact.
[0103] To prepare spherical capsules, a solution containing (substituted) dialcohol cellulose is prepared. The degree of oxidation of the dialcohol cellulose and / or the selection of the substituents can be adjusted to help ensure sufficient miscibility with the solvent or solvent system. In an embodiment, the solution also contains one or more non-polar organic compounds / blowing agents.
[0104] A suitable medium or solvent in which the (substituted) dialcohol cellulose is soluble is described by Berthold et al in J. Appl. Polymer Sci., 2004, 94(2), 424-431, which uses a solution of lithium chloride (LiCl) in dimethylacetamide (DMAc). The concentration of the (substituted) dialcohol cellulose is typically in the range of 0.1 to 10% by weight, for example, in the range of 0.5 to 5% by weight.
[0105] The solution containing the (substituted) dialcohol cellulose also contains a dissolved non-polar organic compound (blowing agent), the typical concentration of which will typically depend on the solubility of the non-polar organic compound in the solvent or solvent system, but will generally be at least 0.5% by weight, for example in the range of 0.5-10% by weight.
[0106] The solution is combined with an anti-solvent, resulting in precipitation of the (substituted) dialcohol cellulose to form a spherical capsule having a hollow interior or core. The hollow core may contain one or more blowing agents and, depending on the porosity or permeability of the (substituted) dialcohol cellulose shell, may further contain a bulk solvent and an anti-solvent.
[0107] The synthesis can be carried out at temperatures ranging from 0 to 100° C., although typically temperatures of 0 to 35° C. are preferred to ensure good solubility and retention of any volatile non-polar organic compounds.
[0108] Pressures in the range of 0.5 to 10 bara can be used. The pressure is typically at least 0.9 bara or at least atmospheric pressure, since the reduced pressure can cause the evaporation of volatile non-polar organic solvents and thus reduce their content in the solution containing the (substituted) dialcohol cellulose.
[0109] The addition can be done dropwise, which promotes the formation of spheres. Furthermore, in an embodiment, the (substituted) dialcohol cellulose-containing solution is added to the antisolvent. The size of the added droplets can affect the size of the spherical capsules formed.
[0110] Without being bound by theory, it is believed that the spherical capsules form as a result of the local formation of a separate phase of the non-polar organic compound due to its insolubility in the antisolvent. Thus, when the solution and the antisolvent are mixed, precipitation of the (substituted) dialcohol cellulose occurs in the area where the separate non-polar organic phase is present. Since the precipitate cannot mix with the fluid phase, this separate non-polar organic phase migrates to the center of the precipitation area and forms a shell of (substituted) dialcohol cellulose around it.
[0111] Capsules can be made to have a range of sizes, e.g., average particle size ranging from 1 μm to 5 mm. Capsules from 0.5 to 5.0 mm can be made in one embodiment. In other embodiments, microsphere capsules can be made to have diameters from 1 to 1000 μm. Microspheres, as opposed to mm-sized spheres, can be made using microfluidic procedures, e.g., as described in Utada et al in MRS Bulleting, 32, 2007, 702-708, and Carrick et al in RCS Advances, 2014, 4, 19061-19067.
[0112] In an embodiment, the spherical or microspherical capsules are expandable. The expanded capsules typically have diameters in the range of 1.5 to 8 times larger than the unexpanded capsules, for example, 2 to 7 or 3 to 6 times the original diameter.
[0113] Particle size is suitably measured using light scattering techniques, for example laser diffraction, such as low angle laser light scattering (LALLS). Such techniques are particularly useful for measuring microspheres. Other techniques include image analysis from photographs or electron micrograph images of spherical capsules before and after expansion.
[0114] To expand the capsules, they can be heated. The required temperature depends on the boiling point of the blowing agent (non-polar organic compound) used. In an embodiment, the temperature is below the melting temperature of the (substituted) dialcohol cellulose and at the same time above the boiling temperature of the blowing agent. Typical temperatures for expansion include in the range of 0-200°C, for example 20-200°C, for example 50-190°C or 100-190°C.
[0115] In another embodiment, the pressure around the capsule is reduced. This can be achieved by reducing the ambient pressure by 10% or more, such as 20% or more or 50% or more. Thus, for example, if the synthesis is carried out at ambient pressure, e.g., 1 bara, a pressure of 0.9 bara or less, e.g., 0.8 bara or less or 0.5 bara or less, can be used. This technique can cause the evaporation or expansion of the blowing agent, expanding the capsule.
[0116] For expansion, the capsules must be in a softened state, which means either exceeding the glass transition temperature (Tg) of the (substituted) dialcohol cellulose, or by keeping the capsules in a moist state so that the walls soften, e.g. by wetting them with antisolvents or water under reduced pressure and / or at elevated temperature.
[0117] At temperatures ranging from 30°C to 200°C, e.g., 30°C to 150°C
[0118] For example, as described in WO 2004 / 056549, WO 2014 / 198532, and WO 2016 / 091847, methods of heating the spherical capsule include direct or indirect contact with a heat transfer medium such as steam or pressurized steam. In further embodiments, direct or indirect contact with other heated gases (e.g., air or nitrogen) optionally mixed with the steam can be used. In yet another embodiment, when indirect heating is used, a liquid heat transfer medium, e.g., heated oil, can be used. In another embodiment, IR radiation can be used to heat the capsule.
[0119] If the blowing agent is relatively non-volatile, heating may be unnecessary. For example, if the synthesis is carried out under high pressure, it may simply be necessary to remove the pressure to ensure expansion of the spherical capsules. In addition, filtering the material from the liquid-phase synthesis mixture can also result in expansion without heating. Conversely, reduced pressure can be used if the blowing agent is relatively non-volatile. In general, pressures in the range of 0.5-1.5 bara and temperatures in the range of 10-200°C can be used depending on the blowing agent and the molecular weight, ring opening, and / or degree of carboxylation or other functionalization of the dialcohol cellulose.
[0120] The expansion properties of the capsules can be evaluated using a thermomechanical analyzer (e.g., Mettler TMA 841) and quantitative data can be obtained from the images using appropriate software, e.g., STARe software. start is the temperature at which expansion begins, and T max is the temperature at which maximum expansion is obtained.
[0121] The capsules can be separated from the synthesis medium by known means, for example, filtration, decantation, or centrifugation.
[0122] The capsules can be provided in the form of a slurry, for example an aqueous slurry, or in the form of dry particles (e.g., a dry powder). The capsules can also be provided in the form of a wet cake, in which the capsules do not dry out completely and remain loosely attached to one another. The capsules can be provided in a non-expanded or expanded form.
[0123] Applications of the microspheres include, for example, the manufacture of paper (e.g., embossed papers, fillers, sizing agents), inks, cork, cementitious compositions, adhesives, foams, insulating materials, coatings, rubber-based products, thermoplastics, thermosets, ceramics, nonwoven composites, fillers, etc. to provide lightweight fillers in such applications.
[0124] Applications for mm-sized spheres include drug delivery, catalysis, insulating materials, packaging, cosmetics, and optical elements. EXAMPLES
[0125] [Synthesis of dialcohol cellulose] Dissolving grade cellulose pulp was provided by Domsjo Fabriker AB, Sweden (Domsjo Dissolving Plus). The cellulose content was 93 wt%, the surface charge was 29 μeq / g, and the degree of polymerization was approximately 780. N,N-Dimethylacetamide (DMAc) and lithium chloride (LiCl) were purchased from Sigma Aldrich, and propane gas was purchased from AGA Gas AB.
[0126] Cellulose fibers were suspended in water at a concentration of 20 g / L and reacted with sodium periodate NaIO4. The amount of sodium periodate used was sufficient to ensure a concentration of 1.35 g / g fiber. In addition, 2-propanol (6.3 vol%) was added. The mixture was left in the dark at a temperature of 50°C for 2 hours. The reaction was stopped by filtration, followed by washing with water until a filtrate conductivity of less than 5 μS / cm was achieved.
[0127] The resulting fibers at this stage had a carbonyl content of 2.62±0.03 mmol / g, corresponding to approximately 22% of the glucose rings being oxidized and therefore ring-opened.
[0128] The fibers were then redispersed in water to a concentration of 8 g / L and reacted with sodium borohydride NaBH4 at a concentration of 0.5 g / g fiber. 0.01 M monosodium phosphate NaH2PO4 was also added to ensure that the pH was maintained at a value below 10. The reaction was allowed to continue for 2 hours at room temperature, after which it was stopped by filtering the reaction and washing the residue with water until the filtrate conductivity was below 5 μS / cm.
[0129] [Capsule synthesis] Cellulose or dialcohol cellulose fibers were swollen in water and made soluble using a solvent exchange procedure as described by Carrick et al. ACS Appl. Mater. Interfaces, 2014, 6(23), 20928-20935. In this method, the water-swollen fibers were suspended in 96% ethanol for 2 days before filtration. The ethanol-swollen fibers were suspended in DMAc, filtered, and resuspended in DMAc a total of four times over a period of 2 days. The DMAc-swollen fibers were then dissolved by preparing a LiCl / DMAc 7 wt% solution by adding lithium chloride, which had been preheated in an oven at 105°C to remove traces of water, over a period of 30 minutes to DMAc heated to 110°C in an oil bath for approximately 30 minutes.
[0130] The solution was cooled to 60° C., at which point the DMAc-treated cellulose fibers were added to the LiCl / DMAc solution to produce a 1.5 wt % cellulose solution. The solution was stirred overnight at room temperature to facilitate dissolution of the pulp.
[0131] The spherical capsules were formed using the solution solidification method described by Carrick et al. in Langmuir 2014, 30(26), 7635-7644. First, 20 mL of the LiCl / DMAc / fiber solution prepared above was saturated with propane gas for 1 h. Then, anti-solvent was added dropwise using a 1.2 mm diameter needle to precipitate mm-sized spherical capsules. The anti-solvents used were selected from methanol, ethanol, isopropyl alcohol, and aqueous mixtures of each of these. Water was also used as a control.
[0132] The capsules were washed 24 hours after precipitation by placing them in fresh non-solvent. The washing step was repeated three times a day for two days using a shaking table and 250 mL of non-solvent.
[0133] The dimensions of the produced capsules were measured from images captured by optical microscope. Parameters were evaluated on 10 capsules. Surface morphology and capsule wall thickness were characterized using a Hitachi S-4800 Field Emission Scanning Electron Microscope (FE-SEM).
[0134] [Expansion experiment] The expansion of the capsule was carried out by exposing it to a decreasing external pressure. Some experiments were carried out in water, where the capsule was placed in a flask filled with water connected to a vacuum pump. To observe the expansion of the wet capsule when removed from water, the capsule was placed in a glass pipette sealed at one end and connected to a vacuum pump at the other. The performance was evaluated using a high-speed camera.
[0135] The properties of capsules made from dialcohol cellulose are shown in Table 1.
[0136] These results highlight that alcohols are suitable poor solvents, although when diluted in water, capsules with improved, and in particular better, gas encapsulation and retention properties are obtained. The best results are seen with alcohols with a polarity greater than that of pure methanol, i.e., a relative polarity of 0.1 to 0.25%.
[0137]
number
[0138]
number
[0139] [Table 1]
[0140] FIG. 1 shows photographs demonstrating the effect of different anti-solvents for (a) Example 4 (methanol only), (b) Example 2 (water / methanol 1:1), (c) Example 6 (ethanol only), (d) Example 5 (water / ethanol 1:1), and (e) Example 3 (water / methanol 1:1.2).
[0141] The mixture of water / methanol as a poor solvent has a ε anti is about 60 to 70,
[0142]
number
[0143] Table 2 compares the properties of capsules prepared from cellulose with those of Example 3. Cellulose capsules were prepared using a procedure similar to that of Example 3, except that cellulose fibers that had not undergone any oxidation / reduction pretreatment were used.
[0144] [Table 2]
[0145] Figure 2 shows optical microscope images of (a) wet and (b) air-dried dialcohol cellulose capsules of Example 3. The wet sample shows thicker walls than the dry sample, however, a distinct core / shell structure is evident.
[0146] Figure 3 shows electron micrographs of (a) freeze-dried and (b) air-dried capsules of Example 3, with micrographs (c) and (d) being cross-sections of each. Micrographs (e) and (f) are magnified images of the highlighted cross-sections of images (c) and (d), respectively. These micrographs highlight the wall thickness difference between the wet and dry samples (freeze-drying of the samples was performed prior to drying to preserve the wet properties of the capsules). In all cases, the core / shell structure is evident.
[0147] FIG. 4 shows the expansion profile of the capsules of Example 3, (a) before and (b) after applying a vacuum to the flask containing the spheres suspended in water, as described above.
[0148] The change in inner diameter from (a) to (b) is a factor of 1.49 (i.e., inner diameter(b) = 1.49 × inner diameter(a)), or an increase of 49%. The change in outer diameter from (a) to (b) is a factor of 1.13, or an increase of 13%.
[0149] FIG. 5 shows the expansion characteristics of the wet (no longer water suspended) capsules of Example 3 (a) before being exposed to reduced pressure in a Pasteur pipette as described above, and (b) thereafter, 20 minutes after their removal from the suspending water.
[0150] Note that since the spheres are no longer in water suspension (see FIG. 4), the polymer shell then does not swell to the same extent and therefore the polymer shell appears to be thinner than that in FIG.
[0151] The radius of the hollow sphere increased by a factor of 1.33 (i.e., a 33% increase in radius).
[0152] FIG. 6 shows spherical capsules made from (i) cellulose and (ii) dialcohol cellulose (a) before and (b) after expansion.
[0153] The dialcohol cellulose hollow spheres expanded to a greater extent, with the (outer) radius increasing by a factor of 1.24 (i.e., a 24% increase) compared to 1.05 (i.e., a 5% increase) for the cellulose capsules. The present invention includes the following embodiments. [1] A spherical capsule comprising a polymer shell surrounding a hollow core, said polymer shell comprising an optionally substituted dialcohol cellulose. [2] the polymer shell is (i) unsubstituted dialcohol cellulose; or (ii) the polymer shell comprises a dialcohol cellulose substituted with one or more substituents according to the following formulas (1)-(7): [ka] (In the formula, C g is a carbon atom that is part of the backbone of the dialcohol cellulose; A is -H, -OR b , and -C(O)OR b Selected from; R a teeth (a) saturated or unsaturated aliphatic groups having 1 to 11 carbon atoms, which may be linear, branched, or cyclic (these include -OH, halide, C 1~4 Alkyl, and C 1~4 alkoxy; 1~4 Alkyl and C 1~4 The alkoxy group is optionally substituted with one or more groups selected from halide and -OH; (b) 5- and 6-membered aromatic rings optionally substituted as described in (a); (c) saturated linear or branched aliphatic
number
number
number
number
number
number
number
number
number
number
number
number
Claims
1. A spherical capsule comprising a polymer shell surrounding a hollow core, the density of the spherical capsule being non-uniform, the density of the polymer shell being greater than the density of the hollow core; The polymer shell comprises: (i) unsubstituted dialcohol cellulose; or (ii) Di-alcohol cellulose substituted with one or more substituents according to the following formulas (1) to (2): 【number】 (In the formula, C g is a carbon atom that is part of the backbone of the dialcohol cellulose; A is -H, -OR b and -C(O)OR b Selected from: R a teeth (a) a saturated or unsaturated aliphatic group having 1 to 11 carbon atoms, which may be linear, branched, or cyclic; (b) 5- and 6-membered aromatic rings; (c) saturated linear or branched aliphatic [0010] Group or cyclic [0025] an aliphatic group, where v is an integer ranging from 1 to 11, w is an integer ranging from 3 to 11, and R c is H, and C 1~4 alkyl); (d) unsaturated linear or branched aliphatic containing "y" double bonds; [0030] A group wherein x is an integer ranging from 2 to 11 and y is 1 or 2; (e) an unsaturated cycloaliphatic group containing "y" double bonds; [0045] A group wherein y is 1 or 2 and w is as defined above; (f) In formula (2), when A is H, R a is selected from the group consisting of: R per occurrence b is H and C 1~4 alkyl groups) A spherical capsule comprising either
2. 2. The spherical capsule according to claim 1, which is expandable by heating and / or by reducing the external pressure.
3. A process for preparing the spherical capsules according to claim 1, comprising the steps of: mixing a solution comprising dissolved optionally substituted dialcohol cellulose and one or more non-polar organic compounds with an anti-solvent to form said spherical capsules; The anti-solvent comprises or consists of one or more compounds and has the following features: (i) the poor solvent has a calculated dielectric constant ε in the range of more than 33.0 and less than 80.1 anti having ε anti is the equation: [0050] (In the formula, ε anti is the calculated dielectric constant of the antisolvent at 20° C.; ε i is the dielectric constant of pure compound i at 20 °C; n is the number of different compounds in the antisolvent; M i is the molar fraction of compound i in the antisolvent. It is calculated by: (ii) the anti-solvent has the formula: [006] Calculated relative polarity values ranging from 0.77 to 0.97, calculated by [0070] (In the formula, [0080] is the calculated relative polarity of the antisolvent; [0090] is the relative polarity of pure compound i at 25° C. and atmospheric pressure compared to water; n is the number of different compounds in the antisolvent; M i is the molar fraction of compound i in the antisolvent. having The process comprising one or more of:
4. The following conditions: (i) The nonpolar organic compound is C 3~8 Alkanes and C 4~12 isoalkanes; (ii) the ε of the poor solvent anti The value is in the range of 34.0 to 80.
0. The process of claim 3, wherein one or more of the following apply:
5. 5. The process of claim 3 or 4, wherein the solution containing the optionally substituted dialcohol cellulose is added to the anti-solvent.
6. 6. The process according to claim 3, wherein the spherical capsules are expandable.
Citation Information
Patent Citations
Processes for the preparation of cellulose beads by reaction of a cellulose substrate with an oxidant
WO2015101786A1